The Effect of Podcast Websites on Digital Metacognitive Competence of Language for Specific Purposes in Hospitality Operations - Kanaan, Khaldoun Naser; Smadi , Adnan Mohammad; Khaleefa, Amal Khalid (Dirasat: Human and Social Sciences, 2025)
Objectives: This paper assesses the impact of podcasting language for specific purposes in hospitality, demonstrates how digital metacognitive competence accounts for more innovative methodologies, and searches for any perceived lifelong knowledge benefits. Methods: Beneath observable laboratory conditions, mixed methods were used. The quantitative data were gathered from participants’ performance, while the qualitative methods examined the impact of podcast websites in the light of the revised Bloom’s taxonomy models. A summative assessment was administered for the selected participants during the experimental set phase, and given a fifteen-week treatment, a further formative assessment was employed. Results: Findings suggest that podcast websites are significant tools for the digital metacognitive competence of language for specific purposes in hospitality operations. Moreover, an institution’s self-directed learning, professional goals, and training policies determine the degree to which podcasts are effective quality methods. Indeed, a relationship is observed between using podcast websites of language for specific purposes and the digital metacognitive competence that works for lifelong knowledge benefits. Conclusions: Industry trainers should adapt their materials to include podcasting websites through URLs of professional languages. Innovative specific measures should pursue a greater understanding of trainees’ self-directed learning preferences.